Α-Bromination of xanthenediones: A mild and efficient approach using N-bromosuccinimide. (2nd January 2022) - Shashi, R.; Begum, Noor Shahina
Abstract: The present work deals with a practically efficient protocol designed for the synthesis of 2, 7-dibromoxanthenediones using N -bromosuccinimide (NBS) in the presence of p -toluene sulfonic acid (PTSA). A combination of NBS and PTSA in chloroform is an efficient system for selective α-bromination of xanthenediones under mild reaction conditions. The main advantage of this method is short reaction duration, mild reaction conditions, easy work up and in addition the method provides excellent yields. All the compounds synthesized were characterized by spectroscopic techniques. GRAPHICAL ABSTRACT: UF0001